Behavior of Framed Masonry and Lightweight Concrete Walls under Lateral Cyclic Loads Analysis by Numerical Models - Nurjannah, Siti Aisyah; Saloma; Saggaff, Anis; Usman, Arie Putra; Rachmah, Mona Fadila; Law, Titanio Erick (Current Approaches in Engineering Research and Technology Vol. 2, 2024)
Infill wall frames are widely used structures, including in earthquake-prone locations. The role of infill walls is often neglected in frame planning. However, infill walls play a role in improving frame performance under cyclic lateral loads. The material forming the infill wall, the type of connector between the column and the infill wall, and the connector distance determine the behavior of the frames. These things need to be analyzed to understand the performance of the frames. This research aimed to obtain the performance level of framed masonry wall (FMW) and framed lightweight concrete wall (FCW) structures to withstand cyclic lateral loads. The research was carried out using finite element-based software. The research results showed that FMW and FCW were highly ductile. FCW had a higher strength than FMW. However, it was not more ductile than FCW. The cumulative energy dissipation of FCW was 56.85% greater than FMW because it could bear lateral cyclic loads better. This indicates that masonry and lightweight concrete have the potential to infill walls for frames in earthquake-prone areas.